Pengaruh Berbagai Jarak Tanam Terhadap Pertumbuhan Dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) Varietas Bima Brebes - Sugiono, Sugiono; Sumarna, Pandu; Laila, Fadhillah; Mahmud, Yudhi; Asad, Faisal Al (Jurnal Agro Wiralodra, 2025)
The shallot plant (Allium ascalonicum L.) is a spice vegetable and the tubers are harvested in the form of layered tubers and are used for consumption as a cooking spice, food industry ingredient and are also commonly used as traditional medicine. The aim of this research is to obtain the best growth and results for Bima Brebes shallot plants at different planting distances. The research was conducted in the rainy season from March 2024 to May 2024. The research location was in Pekandangan Village, Indramayu Sub District, Indramayu District. The method used in this research is an experimental method using a Randomized Group Design (RGD) with a single factor pattern consisting of 5 treatments and 5 replications. The 5 treatments are JT1 = 15 cm x 15 cm, JT2 = 20 cm x 10 cm, JT3 = 20 cm x 15 cm, JT4 = 20 cm x 20 cm, and JT5 = 20 cm x 30 cm. In the growth phase, the best planting distance was obtained in the JT4 treatment. The results obtained the best average yield of onions in the JT5 treatment and the highest tuber weight per plot in the JT2 treatment with an average of 44 g or 140.8 kg/ha or the equivalent of 0.14 tons/ha.